2015
DOI: 10.1080/10962247.2015.1032445
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoke from prescribed burning: Is it a public health concern?

Abstract: Given the increase in PM2.5 concentrations during PB smoke events and its impact on the local air quality, the need to understand the influence of PB smoke exposure on human health is important. This knowledge will be important to inform policy and practice of the integrated, consistent, and adaptive approach to the appropriate planning and implementation of public health strategies during PB events. This will also have important implications for land management and public health organizations in developing ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 48 publications
0
53
0
1
Order By: Relevance
“…The same is likely true for fire smoke, although there has been less research on the topic (Reid et al 2016a(Reid et al , 2016b. Smoke exposure is known to disproportionately affect people with lung diseases and the evidence concerning impacts on heart diseases is emerging (Rappold et al 2012, Haikerwal et al 2015a, 2015b. A few studies have also demonstrated adverse impacts on infants and unborn babies (Jayachandran 2009, Holstius et al 2012, and on people with lower socioeconomic status (Reid et al 2016a, 2016bEnvironmental Research, Rappold et al 2012.…”
Section: Smoke Impacts On Human Healthmentioning
confidence: 99%
“…The same is likely true for fire smoke, although there has been less research on the topic (Reid et al 2016a(Reid et al , 2016b. Smoke exposure is known to disproportionately affect people with lung diseases and the evidence concerning impacts on heart diseases is emerging (Rappold et al 2012, Haikerwal et al 2015a, 2015b. A few studies have also demonstrated adverse impacts on infants and unborn babies (Jayachandran 2009, Holstius et al 2012, and on people with lower socioeconomic status (Reid et al 2016a, 2016bEnvironmental Research, Rappold et al 2012.…”
Section: Smoke Impacts On Human Healthmentioning
confidence: 99%
“…Prescribed burning is widely used in Australia as a means of reducing bushfire risk (Boer et al, 2009); however, these low to moderate intensity fires often take place close to population centres, under weather conditions that are conducive to pollution build up, sometimes on a regional scale (e.g., Williamson et al, 2016, Fig. 2), with potential health impacts on nearby population (Haikerwal et al, 2015). 25 Most of what is known about the VOC emissions from Australian temperate forest fires to date comes from opportunistic measurements of bushfire plumes impacting measurement sites such as the University of Wollongong (Paton-Walsh et al, 2005Rea et al, 2016) or the Cape Grim Baseline Air Pollution Station (Lawson et al, 2015) or captured from space using satellite sensors (Young and Paton-Walsh, 2011;Glatthor et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While the potential hazard from prescribed fire smoke has been recognised (Haikerwal et al, 2015), most of our understanding of prescribed fire smoke exposure stems from research into wildfires (Reisen and Brown, 2009). There have been studies of firefighter exposure at prescribed fires (Miranda et al, 2010;Reisen et al, 2011;Adetona et al, 2013) but the effect of prescribed burning on smoke exposure to the local community has rarely been addressed in research (Reisen and Brown, 2009).…”
Section: Introductionmentioning
confidence: 99%